Religious Existentialism as a Countermeasure to Moralistic Therapeutic Deism - Valcova, Katarina; Pavlikova, Martina; Roubalova, Marie (Communications - Scientific Letters of the University of Zilina, 2016)
Moralistic Therapeutic Deism (MTD) is a new spiritual trend that is increasingly changing the religious landscape of in the Euro-American cultural provenience. Though appealing to the generation of 'emerging adults' (age 18-25), MTD results in undesirable life-outcomes that prompt religious scholars, theologians, and sociologists to carefully study its roots, expressions, and possible alternatives. Using S. Kierkegaard's religious existentialism as a case study, the authors argue that religious existentialism has the potential to face the detrimental effects of MTD and to reinvigorate stagnating religious communities.
Keywords: religious existentialism; tradition; moralistic therapeutic deism; consequential faith; Kierkegaard